THE MUNDELL-FLEMING MODEL IN MODERN OPEN ECONOMIES: A SYSTEMATIC REVIEW - Pratama, Aditya; Novalia, Susi; Syahmi, Afdhanil; Jamaluddin, Iqbal (Edunomika Journal : Studies In Education And Development Economics, 2026)
This systematic review aims to map the evolution and relevance of the Mundell-Fleming Model (MFM) amidst the complex dynamics of the modern global economy. Adapting the PRISMA protocol, this study extracted and synthesized 25 primary articles (2015–2026) from Scopus, Google Scholar, and Sinta databases. The review results show that the MFM is not obsolete, but rather undergoing a metamorphosis. Rigid assumptions such as the Policy Trilemma are now proving to be more flexible, significantly influenced by domestic political forces, innovations in banking digitalization, and the paradigm of global currency dominance. The novelty of this article lies in the integration of classical macroeconomic debates with previously marginalized contemporary dimensions, such as the green energy transition and political economy. Consequently, this research not only guides policymakers in developing countries to formulate robust fiscal-monetary instruments to withstand crisis shocks but also contributes fundamentally to the development of economic science and education. In the educational realm, these findings urge educators to transition from teaching static macroeconomic models to adaptive multidimensional analytical frameworks, so that students are equipped with a conscience and critical reasoning sensitivity to the empirical realities of real-world financial markets.